2015
DOI: 10.1680/macr.14.00192
|View full text |Cite
|
Sign up to set email alerts
|

Paraffin wax as an internal curing agent in ordinary concrete

Abstract: Curing of concrete involves maintaining satisfactory moisture content during early stages to develop the desired properties. Properly cured concrete has improved durability and surface hardness, and is less permeable. Prevention of loss of moisture is important not only for strength development but also to prevent plastic shrinkage, for decreased permeability and to improve resistance to abrasion. Good and complete curing is not always practical for several reasons, particularly in higher grade concretes. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The same trend is also seen in other grades of concrete. The results in [14,22] also showed that 1 day curing at 28 days has less strength when compared with 28 days curing strength, almost the same percentage of loss is noticed. In Figure 13, it is also noticed that the samples kept outside the laboratory have a little bit higher strength when compared with the samples kept inside the laboratory.…”
Section: F Compression Strengthmentioning
confidence: 81%
See 3 more Smart Citations
“…The same trend is also seen in other grades of concrete. The results in [14,22] also showed that 1 day curing at 28 days has less strength when compared with 28 days curing strength, almost the same percentage of loss is noticed. In Figure 13, it is also noticed that the samples kept outside the laboratory have a little bit higher strength when compared with the samples kept inside the laboratory.…”
Section: F Compression Strengthmentioning
confidence: 81%
“…At 7th day the samples cured for 1 day have more water loss as compared with the samples cured for 6 days. The same trend of water loss for grade 40 and grade 60 resulted in [14,22]. The samples kept outside the laboratory after each curing day did not show a uniform trend of water loss as shown in Figure 6.…”
Section: Water Loss From Normal Strength Concretementioning
confidence: 83%
See 2 more Smart Citations
“…Unlike traditional curing, self-curing concrete removes moisture from the concrete's water evaporation, allowing it to hold more water. Polymeric glycols and paraffin wax are examples of hydrophilic materials that self-cure [3,4]. Liquid paraffin wax as a self-curing agent, this study compares it to alternative curing regimens that simulate traditional curing procedures [5].…”
Section: Introductionmentioning
confidence: 99%